Crewtime in a Space Greenhouse based on the Operation of the EDEN ISS Greenhouse in Antarctica - Zabel, Paul; Zeidler, Conrad; Vrakking, Vincent; Dorn, Markus; Schubert, Daniel (2019)
The EDEN ISS project partners deployed a space greenhouse analogue at the Neumayer Station III in Antarctica in January 2018. The greenhouse is incorporated in two interconnected 20 foot shipping containers and positioned around 400 meters away from the research station. All subsystems required for plant cultivation are inside this so called Mobile Test Facility. The cultivation area of around 12.5 m² is arranged in a shelf-like structure in one of the containers, while the other container houses the subsystems and a small working area. Between February and November 2018 one of the authors was the only on-site operator of the greenhouse. In that time it was his responsibility to cultivate various plants and to execute numerous experiments. One of the experiments was the determination of the crewtime required for plant cultivation. A formula to calculate the crewtime use inside a space greenhouse has been developed. This paper also presents crewtime values for various activities related to the operation of a space greenhouse. The focus is on the tasks related to plant cultivation such as sowing, pruning, harvesting and cleaning. Crewtime has been measured independently for different crop species, because each crop species requires different tasks to be performed during cultivation. Additionally, the task schedule and related crewtime of complete workdays have been documented at several occasions during the nine months of operation of the EDEN ISS greenhouse in Antarctica.